2022
DOI: 10.3389/fdata.2022.992620
|View full text |Cite
|
Sign up to set email alerts
|

The role of gender in providing expert advice on cyber conflict and artificial intelligence for military personnel

Abstract: This article draws upon original qualitative interview data with Norwegian male and female cyberengineer cadets at the Norwegian Cyber Defense Academy, who could in the future be working with AI-enabled systems in a variety of positions throughout the Norwegian military. The interviews explored how these cadets feel they as cyberengineers will be perceived in their future positions in the military, what challenges they feel they may face, and how gender may play a role in this. Different cyberengineers express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Due to conducting the study in a security setting, we did not ask participants to provide information on their sexes. While the sex of participants is commonly underreported in cybersecurity studies (Ask et al, 2021a ), a recent study suggested that sex may play a role in communication among cyber engineers (Fisher, 2022 ). Future studies should therefore make an effort to also assess whether findings are differentially influenced by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Due to conducting the study in a security setting, we did not ask participants to provide information on their sexes. While the sex of participants is commonly underreported in cybersecurity studies (Ask et al, 2021a ), a recent study suggested that sex may play a role in communication among cyber engineers (Fisher, 2022 ). Future studies should therefore make an effort to also assess whether findings are differentially influenced by sex.…”
Section: Discussionmentioning
confidence: 99%